Hubungan Konsep Diri dan Kecerdasan Emosional Terhadap Hasil Belajar Biologi Siswa Di Kelas XI IPA SMA - Harahap, Siti Khadizah; Sipahutar, Herbert (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
The purpose of this study was to determine the studentâs self concept relationship relationship and emotional intelligence on studentâs achievement in eleventh science grade SMA Se-kota Tebingtinggi Academic Year 2016/2017. Questionnaire was used to know the self concept and emotional intelligence, while the learning out comes gotten from studentâs biology exam score in last semester document. From the results of the test data requirements known that the relationship of self-concept and emotional intelligence on students achievement, that calculated by testing the coefficient of determination,Â percentage of contribution obtained 59,29% for self-concept of students, 54,76% for the emotional intelligence of learning, and 62,4% for the emotional intelligence and self-concept on student biology achievement. From the research, results can be obtained that Ha accepted because there is a significant relationship between self-concept and emotional intelligence on studentâs achievement in eleventh science grade SMANegeri Se-kota Tebingtinggi Academic Year 2016/2017.